2008
DOI: 10.1002/joc.1758
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations of precipitation during the warm season over China

Abstract: ABSTRACT:The spatial distribution and seasonal change of diurnal variations of precipitation during the warm season (May-September) over China were analysed using hourly data from 62 rain gauges during 1954-2001. Nocturnal precipitation predominates for the stations over the Tibetan Plateau as well as in south-west and north-west China. For stations to the east of about 110°E, daytime precipitation predominates in the northern and southern parts, whereas nocturnal precipitation predominates in the middle and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 44 publications
3
80
2
1
Order By: Relevance
“…Power spectrum analyses of P SEC and LIS SEC variations during the 1998-2009 summer periods also show the diurnal and semi-diurnal as the two dominant oscillation periods (Figure 2(a) and (b) respectively). Yin et al (2009) suggested that the hourly rainfall records from 62 selected rain gauges over China can be well explained by their S1 and S2 harmonics with a 90% confidence threshold. Consistent with Yin et al (2009), it is found that ∼97% and 98% of the variance of P SEC and LIS SEC respectively (thick grey solid line in Figure 2(c) and (d) respectively) is explained by the variance of their combining S1 and S2 harmonics (thin solid line with open circles).…”
Section: General Characteristics Of Diurnal Variations Over Secmentioning
confidence: 99%
See 4 more Smart Citations
“…Power spectrum analyses of P SEC and LIS SEC variations during the 1998-2009 summer periods also show the diurnal and semi-diurnal as the two dominant oscillation periods (Figure 2(a) and (b) respectively). Yin et al (2009) suggested that the hourly rainfall records from 62 selected rain gauges over China can be well explained by their S1 and S2 harmonics with a 90% confidence threshold. Consistent with Yin et al (2009), it is found that ∼97% and 98% of the variance of P SEC and LIS SEC respectively (thick grey solid line in Figure 2(c) and (d) respectively) is explained by the variance of their combining S1 and S2 harmonics (thin solid line with open circles).…”
Section: General Characteristics Of Diurnal Variations Over Secmentioning
confidence: 99%
“…Yin et al (2009) suggested that the hourly rainfall records from 62 selected rain gauges over China can be well explained by their S1 and S2 harmonics with a 90% confidence threshold. Consistent with Yin et al (2009), it is found that ∼97% and 98% of the variance of P SEC and LIS SEC respectively (thick grey solid line in Figure 2(c) and (d) respectively) is explained by the variance of their combining S1 and S2 harmonics (thin solid line with open circles). In addition, it is also noted from Figure 2(c) and (d) that the variance of S2(P) SEC and S2(LIS) SEC contributes to ∼30% and 35% of the variance of P SEC and LIS SEC respectively.…”
Section: General Characteristics Of Diurnal Variations Over Secmentioning
confidence: 99%
See 3 more Smart Citations